Design optimization of speed increaser installed on wind power generator / Wang Lesu - Wang, Lesu (2019)
Wind power speed increaser is a low-speed and heavy-duty gear transmission equipment. It serves as one of the important components in wind turbine. The working environment and characteristics determine that it often breaks down after long term operation. Therefore, the design, reliability and dynamics of wind power speed increaser are highly demanded. Thus, the static analysis & dynamic analysis are used to check the safety of increaser and optimization are used to improve the reliability of it. This study used Shigley's design method and computational analysis (FEA) to analyze the feasibility of the design. Safety factor was calculated by Shigley's design method; static analysis, dynamic analysis and design optimization were carried out by using ANSYS Workbench 18.0 software. The speed increaser was analyzed on safety factors, maximum stress & maximum deformation of gears, shafts, keys and casing. Based on the Shigley's design methods, the results have shown that gears, shafts, keys and bearing do not have any failure. For computational analysis, all gears, bearing and casing also do not indicate any failure in static analysis and dynamic analysis. However, it is noted that the equivalent stress of shaft III is too large reaching 1148.5 MPa and the fatigue safety factors of shaft III and key III is 0.33 and 1.03, respectively, which indicates fatigue failure is likely happen in these machine components. The problems are mainly focused on the strength failure. Design optimization is focused on reducing stress and increasing safety factor. The diameter and fillet of shaft, length and width of key are used as input parameters. The best candidate from the design optimization analysis showed a positive result by increasing diameter of shaft and increasing length and width of key. The fatigue safety factor of shaft increased to 1.4 and stress reduces to 279.64MPa. The fatigue safety factor of key also increased to 1.48.